Doença pulmonar obstrutiva crônica - Tanni, Suzana Erico [UNESP]; Coletta, Jacob Antônio Della [UNESP]; Coelho, Liana Sousa [UNESP]; Godoy, Irma de [UNESP] (My University, 2007)
Chronic obstructive pulmonary disease (COPD) is considered the forth cause of death in the world. The present review summarizes the epidemiologic and risk factors to the disease. Emphasizing the diagnostic, pulmonary function, radiological alterations and blood gases. According to the current guideline recommendations, the authors reviewed the classification and treatment. © Copyright Moreira Jr. Editora. Todos os direitos reservados.
Chronic obstructive pulmonary disease
Keywords: Chronic obstructive pulmonary disease; Dyspnea; Lung disease; aminophylline; bronchodilating agent; corticosteroid; fenoterol; formoterol; ipratropium bromide; methylxanthine; oxygen; salbutamol; salmeterol; terbutaline; author; blood gas; chronic obstructive lung disease; differential diagnosis; disease classification; disease exacerbation; human; lung function; oximetry; oxygen therapy; physical examination; practice guideline; radiodiagnosis; radiology; risk factor; spirometry; symptom